UK professional accounting bodies (PAB): Members’ unethical behaviors and exclusion - Ismail Adelopo (21976697) (2022)
Although previous studies have explored the disciplinary procedures and sanctions by PABs, the focus of these studies has often been generalized to all forms of infringements. This has prevented specific attention on the most severe ethical breaches by PAB members, that is, offences leading to exclusion. Consequently, we do not know their prevalence, the features of these behaviors or the motivating factors for their perpetration by members of the UK's PABs. Clarity on these issues is in the public interest given the centrality of the role of the accounting profession to the efficient functioning of the financial system. We used the fraud triangle theory to shed light on these issues. Our analysis is based on the entire population of 141 serious cases that led to members’ exclusion. We developed an analytical framework that focused on the nature of the infringements, their prevalence amongst the PABs, and the variety of explanations provided by the culprits. Our analysis shows that criminal convictions and breach of ethical guidance are the two major causes of exclusion. Our findings have implications for the PABs in their attempts to ensure their members’ ethical behavior and the adequacy of their disciplinary process. Other Information Published in: Journal of Corporate Accounting & Finance License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jcaf.22547